The Effectiveness of U-Dictionary as Learning Media to Improve Students’ Vocabulary Achievement at Senior High School - Adinda , Febi; Rahayu, Endang Mastuti (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Vocabulary is very important in learning English. Students learning grammar without vocabulary will have a hard time understanding what they are trying to say. Meanwhile when studying English as a second language, people must have a sufficient vocabulary to express themselves and learn a wide variety of words to avoid being detected when they read, write, listen, or speak in English. This study aims to analyze the effectiveness U-Dictionary as media to students’ vocabulary achievement at senior high school at tenth grade. In this study, the design used quantitative pre-experimental. Population In this study that was students at tenth grade in senior high school, divided among all fifteen classes using the technique of random sampling. Instrument in this study used test in objective form. The result could be concluded was proved that the alternative hypothesis (Ha) accepted, meanwhile the null hypothesis rejected (H0) rejected. After using the t-test formula after the test, where the t-test value (3053) was greater than the table value t (1.994) at the 0.05 or 5% significance level in the two-tailed test with df 70. The conclusion showed the U-Dictionary can effective to student’s vocabulary achievement at senior high school.